ANALISIS RASIO KEUANGAN DAN COMMON SIZE UNTUK MENILAI KINERJA KEUANGAN PERUSAHAAN KOSMETIK DAN PERALATAN RUMAH TANGGA YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2013-2015 - Anastasya, Shinta; Hidayati, Cholis (JEA17: Jurnal Ekonomi Akuntansi, 2019)
ABSTRACTFrom the Common Size report on the financial position of PT. Akasha Wira Internasional, Tbk. PT. Mandom Indonesia, Tbk. PT. Martina Berto, Tbk. PT. Mustika Ratu, Tbk. And PT. Unilever Indonesia, Tbk can be seen that the average total current assets owned by PT. Martina Berto Tbk of 72.5% is the highest compared to the others. But in the highest average fixed assets owned by PT. Unilever Indonesia Tb 56.5% compared to other cosmetics companies. Then for the highest average current debt owned by the company PT. Unilever Indonesia Tbk by 63.2% compared to other cosmetics companies, on the contrary the highest average long-term debt owned by the company PT. Akhasa Wira International Tbk is 15.0% compared to other cosmetics companies. From the Common Size profit and loss table of PT. Akasha Wira Internasional, Tbk. PT. Mandom Indonesia, Tbk. PT. Martina Berto, Tbk. PT. Mustika Ratu, Tbk. And PT. Unilever Indonesia, Tbk can be seen that the average cost of goods sold by the company PT. Mandom Indonesia Tbk is the highest average compared to other cosmetics companies which is 62%, which means PT. Mandom Indonesia Tbk has an unfavorable profit rate because if the cost of goods sold is higher it will have an impact on profit decline, conversely if the cost of goods sold is low it will increase the company's profit. Similarly, the average gross profit owned by PT. Mustika Ratu Tbk has the highest average compared to other cosmetics companies, which is 57%. And for the highest average net profit owned by PT. Unilever Indonesia Tbk is compared to other cosmetics companies, which is 17%, which means the company is able to perform well so as to produce an increase in profits.Keywords: Financial Ratios, Common Size and Financial Performance